Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Video Interaktif terhadap Hasil Belajar Mata Pelajaran Projek Kreatif dan Kewirausahaan di SMK PGRI 3 Badung - I Made Ardita; I Made Yudana; Kadek Rihendra Dantes (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to 1) find out the differences in learning outcomes of creative and entrepreneurial project subjects before applying the interactive video media-assisted problem-based learning model, 2) knowing the differences in learning outcomes of creative and entrepreneurial project subjects after applying the problem-based learning model assisted by interactive video media, 3) knowing the significant influence of the problem-based learning model assisted by video media interactive for grade XI students majoring in Hospitality at SMK PGRI 3 Badung in 2023/2024. This research is quantitative research with a type of research, namely quasi-experiment (quasy experiment). The results showed that: 1) The learning outcomes of creative and entrepreneurial project subjects before applying the interactive video media-assisted problem-based learning model were obtained a range value of 21, a minimum value of 56 and a maximum value of 77, at a mean value of 66.59, a standard deviation of 6.265 and a variance of 39.248, 2) Student learning outcomes after applying a problem-based learning model assisted by video media interactive where the range value is 12, at a minimum value of 80 and a maximum of 92, the mean value is 85.97, the standard deviation is 3.262 and the variance value is 10.638, 3) There is an influence of the problem-based learning model assisted by interactive video media on the results of student learning creative and entrepreneurial project subjects where Pair 1 obtained a significance value (2-tailed) of 0.000 smaller than 0.05, then it means that there is a difference in the average learning outcomes of students for the experimental class Pre-Test with the experimental class Post-Test. In the output of Pair 2 obtained a significance (2-tailed) of 0.000 smaller than 0.05, so it means that there is a difference in the average learning outcomes of students for the control class Pre-Test with the control class Post-Test.